Sensitivity and Specificity of MRI in diagnosing Meniscal Injuries – Results from a Developing Country (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To assess the sensitivity and specificity of MRI in diagnosing meniscal injuries at a tertiary care center in Karachi, catering to patients from across Pakistan. Methods: A cross sectional study was conducted at the Aga Khan University Hospital, Karachi, between August 2019 to July 2020 including all patients between the age of 18 - 70 years who were treated for meniscal injuries and had an MRI scan before arthroscopic management. MRI reports of all patients were reviewed from our institutional database and arthroscopic findings were then reviewed from the operative notes. Sensitivity, specificity, and positive and negative predictive values of MRI were calculated using standard formulas in comparison to arthroscopic findings which was considered as gold standard. Results: A total of 82 patients were included in the study, out of which 71.7% were males and the most common mechanism of injury was noted to be sports related. Overall accuracy for medial meniscus injuries was calculated to be 89.8% with sensitivity and specificity values of 96.2 and 80.5% respectively. For lateral meniscus injuries, the overall accuracy was calculated to be 94.6% with a sensitivity of 91.7% and specificity of 95.7%. Conclusion: MRI has a high sensitivity and specificity for diagnosing meniscal lesions even in developing countries and should be done in all preoperative patients.